Hotel industry in Ukraine embraces green revolution - Ohorodniichuk, Olena; Dotsenko, Viktor; Shydlovska, Olena; Ishchenko, Tatiana (My University, 2013)
The article argues the relevance and importance of environmental development of the hotel industry in Ukraine. The current state of the eco-hotels in Ukraine, their features, challenges and opportunities for development were also analyzed in this article.
Keywords: eco-hotel; еко-готелі; greening; екологізація; hotel industry; готельне господарство; environmental certification; екологічна сертифікація; кафедра готельно-ресторанної справи